Rodinný dům u farmy - Vondráková, Pavlína (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Bakalářská práce se zabývá projektovou dokumentací rodinného domu u farmy na úrovni dokumentace pro stavební povolení stavby. Rodinný dům bude situován v kraji Vysočina, obci Luka nad Jihlavou - Svatoslav, katastrálním území Svatoslav nad Jihlavou. Objekt je zasazen do mírně svažitého terénu a je kladen důraz na celkový dojem stavby a její splynutí s okolní krajinou a splynutí s navrhovaným komplexem budov farmy. Dům má dvě bytové jednotky. Hlavní bytová jednotka je určena pro čtyřčlenoou rodinu a druhá je určena jako bytová jednotka pro dva hosty. Stavba je navržena jako zděná konstrukce, má dvě nadzemní a jedno podzemní podlaží. Svislé konstrukce jsou v nadzemní části z konstrukčního systému HELUZ, v části podzemní ze ztraceného bednění. Vodorovné konstrukce jsou tvořeny z jedné části ze stropního systému SPIROLL, z druhé části konstrukcí dřevěného stropu. Konstrukce střechy je tvořena sedlovou střechou se zabudovanými trapézovými vikýři a použitým střešním systémem KM Beta.

The bachelor thesis deals with project documentation of a family farmhouse. The project documentation is intended for building permit. The family house will be located in region of Vysočina, municipality of Luka nad Jihlavou and cadastral area of Luka nad Jihlavou. The building is situated in moderate steep terrain. Important goal is complex effect of the building and its merging with surrounding environment and with designed area of the other farm buildings as well. The house is consisting of two housing units. The main housing unit is designed for family of four members and the second unit is designed as housing for guests. The building is designed as masonry construction with two floors above ground and one floor below ground. For vertical structures above ground is HELUZ system used and for vertical structures below ground is permanent formwork used. Horizontal structures partly consist from SPIROLL ceiling system and partly from wooden ceiling structures. For construction of the roof, which is designed as gabled roof with built-in trapezoid dormers, is KM Beta roof system used.
Family house at the farm
Keywords: Rodinný dům u farmy; projektová dokumentace; sedlová střecha; dřevěný strop; zděná stavba; HELUZ; KM Beta; SPIROLL.; Family farmhouse; project documentation; gabled roof; wooden ceiling; masonry construction; HELUZ; KM Beta; SPIROLL.